Erelzi® – biosimilar of etanercept in the treatment of rheumatic diseases and psoriasis (Resolution of the Expert Panel) - V. I. Mazurov; A. M. Lila; T. V. Korotaeva (Современная ревматология, 2021)
Introduction of biosimilars of biological disease-modifying antirheumatic drugs (bDMARs) into clinical practice has significantly expanded the availability of bDMARD therapy for a wide range of patients with chronic immuno-inflammatory diseases.In 2020, the first biosimilar etanercept Erelzi®, was registered in the Russian Federation. On May 22, 2021, an interdisciplinary Expert panel meeting was held on the use of Erelzi® for the treatment of rheumatic diseases and psoriasis. The leading Russian rheumatologists and dermatologists participated in this meeting. In the resolution of the Expert panel, it was stated that according data from randomized clinical trials and real clinical practice and due to low immunogenic potential of Erelzi, it can be used in initial therapy and in switching from other bDMARDs therapy in patients, who develop adverse reactions or face loss of their therapy effectiveness.